2014
DOI: 10.7860/jcdr/2014/10090.5082
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Status in Type 2 Diabetic Patients: Relation to the Progression of Diabetic Nephropathy

Abstract: Background and Objectives: Zinc deficiency often occurs in patients with diabetes. Therefore, the relationship between zinc status and progression of nephropathy in diabetes has been explored. Materials and Methods:Total 300 diabetic patients and 100 non-diabetic healthy subjects (age matched) were selected followed by informed consent and divided into five groups as I: non-diabetic normotensive control; II: diabetic normotensive; III: diabetic hypertensive; IV: diabetic normotensive with microalbuminuria; V: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…Brain tissues require a high level of glucose energy intake (about 20%) in humans and mammals and brain energy deficiency might be a contributing factor of abnormal brain function in AD [112]. However, the most plausible common factor between AD and T2D is deficiency of IDE activity due to zinc deficiency [31], [33]. Zinc is an integral part of IDE, which is a zinc protease, involved in both IDE gene expression and required for IDE activity.…”
Section: Methods Of Treating Alzheimer's Disease and Type 2 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain tissues require a high level of glucose energy intake (about 20%) in humans and mammals and brain energy deficiency might be a contributing factor of abnormal brain function in AD [112]. However, the most plausible common factor between AD and T2D is deficiency of IDE activity due to zinc deficiency [31], [33]. Zinc is an integral part of IDE, which is a zinc protease, involved in both IDE gene expression and required for IDE activity.…”
Section: Methods Of Treating Alzheimer's Disease and Type 2 Diabetesmentioning
confidence: 99%
“…IDE is a zinc protease and the most well known enzyme that degrades both insulin and extracellular and intracellular Aβ [30]. Zinc deficiency which has been noted in both AD and T2D patients [31], [32], [33], which causes IDE deficiency since zinc is an absolute requirement for IDE synthesis. Since IDE deficiency contributes to the induction of some forms of AD [34], [35], increasing degradation of extracellular Aβ by IDE or similar enzymes would be beneficial for the possible prevention and/or treatment of AD [36].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with low serum zinc concentration had a higher risk for death from CHD than patients with high serum zinc level (Figure 1). More recent studies diabetic patients from Iraq, China and Japan also confirmed that lower serum zinc level in T2D patients was related to higher prevalence of diabetic microvascular complications, and represented as an independent risk factor for diabetic nephropathy [11][12][13]. Patients with lower zinc level were more likely to have a longer duration of diabetes, poorer glucose control and worse β cell function [12].…”
Section: Introductionmentioning
confidence: 91%
“…Patients with lower zinc level were more likely to have a longer duration of diabetes, poorer glucose control and worse β cell function [12]. Advancing diabetic nephropathy represented by decreasing GFR and increasing microalbuminuria is associated with lower serum zinc levels [11]. Low serum zinc to copper ratio was positively associated with renal dysfunction in all subjects and poor glycemic control in patients with T2D [13].…”
Section: Introductionmentioning
confidence: 99%